An Islamic Education Based Habituation Model for Shaping Students’ Healthy Living Behavior - Mahrus (LPPM Universitas Ibn Khaldun, Bogor, 2025)
This study aims to describe the Islamic education based habituation model in shaping healthy living behavior at MI Unggulan Nuris Jember. The research was conducted from July to September 2025 using a descriptive qualitative approach. Data were collected through in-depth interviews, participatory observations, and documentation involving five purposively selected key informants: the principal, Islamic education teacher, dormitory supervisor, and students. Data were analyzed using Miles and Huberman’s interactive model, which includes data reduction, data display, and conclusion drawing, with validity ensured through source and method triangulation. The findings show that the habituation model is implemented through four main pillars: teacher exemplification, routine activities, religious habituation, and value reinforcement through a reward–punishment system. Its distinctive practices include proper waste disposal, nutritious meals prepared by the boarding kitchen, the poskestren (Islamic health post), ro’an (cleanliness duty), and room cleanliness competitions. The model effectively nurtures students’ healthy living behavior naturally and sustainably through the internalization of Islamic values of iman (faith), amanah (responsibility), and thaharah (cleanliness).